2005
DOI: 10.1007/s11910-005-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular disorders and sleep

Abstract: Neuromuscular disorders are caused by the primary involvement of the motor unit. In these patients, sleep-disordered breathing (SDB) due to respiratory muscle weakness is often encountered during sleep. Because there is a tendency to overlook this disorder, all patients with neuromuscular disorders should be questioned about SDB. Overnight polysomnography is the best investigation for SDB and nocturnal desaturations. In the management of these patients, noninvasive intermittent positive pressure ventilation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS), postpolio syndrome, myotonic dystrophy, myasthenia gravis, Duchenne muscular dystrophy (DMD), and other myopathies are among the common NMD associated with sleep-related complications, and different types of sleep disturbances may predominate in specific neuromuscular diseases. SDB is reported in 17-76% of patients with ALS, and in 31% of patients with postpolio syndrome [7 ]. A study of children with DMD [8 ] recently showed that obstructive sleep apnea (OSA) was present in 31% and hypoventilation in 32% of patients.…”
Section: Prevalence Of Sleep Disorders In Neuromuscular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyotrophic lateral sclerosis (ALS), postpolio syndrome, myotonic dystrophy, myasthenia gravis, Duchenne muscular dystrophy (DMD), and other myopathies are among the common NMD associated with sleep-related complications, and different types of sleep disturbances may predominate in specific neuromuscular diseases. SDB is reported in 17-76% of patients with ALS, and in 31% of patients with postpolio syndrome [7 ]. A study of children with DMD [8 ] recently showed that obstructive sleep apnea (OSA) was present in 31% and hypoventilation in 32% of patients.…”
Section: Prevalence Of Sleep Disorders In Neuromuscular Diseasesmentioning
confidence: 99%
“…Bilateral phrenic nerve involvement due to local causes or as part of diffuse polyneuropathy (e.g. Charcot-MarieTooth disease, Guillain-Barré syndrome) is well recognized as a cause of nocturnal hypoventilation, oxygen desaturation, frequent arousals, and secondary daytime somnolence [7 ].…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%
“…Solunum dürtüsünde azalma uyku sırasında belirginleşir. 23 Paradoksal abdominal hareketi olan hastalarda, diyafragmanın solunuma katılımında anlamlı azalma ve dolayısıyla hem REM hem de non-REM uykusunda daha büyük oksijen desatürasyonu ortaya çıkar. Restriktif hastalıkta kan gazlarında ilk anlamlı bozukluk, REM uykusu sırasındaki hiperkapni ve hipoksidir.…”
Section: Tablo 2 Solunum Kas Zayıflığı Ile Ilişkili Problemlerunclassified
“…Knowledge of respiratory anatomy and physiology allows an understanding of how pharyngeal muscle weakness predisposes to airway collapse and obstructive hypopnea or apnea, whereas weakness of the diaphragm produces nonobstructive hypoventilation maximal during sleep. [1][2][3]9,10 Reductions in muscle tone and chemosensitivity, especially during REM sleep, mean that any superimposed weakness of upper airway muscles, or medications that further reduce tone, reduce airway patency. Depending on severity, this could result in an increase in upper airway resistance, hypopnea, or even apnea.…”
Section: Sleep Disorders In Neuromuscular Diseasesmentioning
confidence: 99%